Genes codificadores de fatores de virulência, inflamação e avaliação nutricional da infecção intestinal associada com Escherichia coli enteroagregativa em crianças de Fortaleza, Ceará, Brasil - Lima, Ila Fernanda Nunes (2008)
Enteroaggregative Escherichia coli (EAEC) is a pathotype of diarrheagenic E. coli, which has increasingly been identified as an etiological agent of diarrheal disease. This purpose of this study is to determine the prevalence of EAEC and examine the importance of some virulence-related genes in the severity of the diarrheal disease caused by this microorganism, and further evaluate the impact of these infections on intestinal inflammation and the nutritional status of poor children from Fortaleza, Ceara. Children aged 2 to 36 months, with and without an occurrence of diarrhea in the previous 14 days, had their anthropometric data evaluated and their stools collected. Diagnosis of EAEC was done by polymerase chain reaction (PCR) of the aaiC (chromosomal) and aatA (plasmidial) genes. Positive samples were further analyzed for the presence of the virulence genes aggR (transcription regulator), aap (dispersin), pic (enterotoxin), pet (enterotoxin) and astA (enterotoxin). The nucleotide sequence of aggR gene was also analyzed by sequencing. Aliquots of stool samples were quantified for lactoferrin (LFF) and cytokines (IL-4, IL-10, TNF-α e IFN-γ) by enzyme-linked immunosorbent assay (ELISA). This study analyzed 83 children with diarrhea (cases) and 83 children without diarrhea (controls). EAEC was found in the same proportion in both groups (41.0%). Children with diarrhea presented with significantly reduced skin thickness, body mass index and weight-for-age (WAZ) and weight-for-height (WHZ) z-scores. However, the presence of the bacteria was not associated with changes in the analyzed anthropometric measures. Among the positive samples for EAEC, there was no difference in the presence of the isolated virulence genes in the children with or without diarrhea. Observing the frequencies of these genes in combination, EAEC strains carrying the aggR, aap, pic, pet and astA genes together were isolated in significantly higher frequencies from sick children when compared to EAEC strains expressing only aggR, aap, pic, and astA (excluding pet). Nucleotide sequence analysis of the aggR gene presented 27 polymorphisms of a single nucleotide (SNPs), distributed among five case samples and three control samples. More than 80.0% of studied children had intestinal inflammation characterized by elevated levels of LFF, regardless of the presence of illness and EAEC. All children with diarrhea associated with EAEC presented with high concentrations of LFF. Basal levels of fecal cytokines were observed among children from both groups. Variability in the presence of the evaluated virulence factors confirms the heterogeneity of EAEC strains. The combination of the virulence related genes expressed showed that pet has an association with illness caused by EAEC. The infection by this bacterium did not cause significant impact on the anthropometric index analyzed. The high concentrations of LFF observed suggest that there may be additional factors triggering the inflammatory process.